An ANALISIS EFEKTIVITAS PROGRAM PROMOSI KESEHATAN RUMAH SAKIT (PKRS) DALAM MENINGKATKAN PENGETAHUAN PASIEN RAWAT JALAN DI RSU. BINA KASIH MEDAN - DALIMUNTHE, SELVIA YOLANDA (LPPM Universitas Awal Bros, 2025)
The implementation of health promotion in Hospitals (PKRS) is very important to be implemented in Hospitals, which is useful for increasing the understanding of patients, patient families and visitors in Hospitals. The consequences that arise if PKRS is not implemented include the high number of patients with unhealthy behaviors that have the potential to cause infectious diseases, the large health budget for hospitals (more than 70%), challenges in improving patient quality and safety, and increasing nosocomial infections that pose a risk to health. The results of this study are statistical tests showing that there is a unidirectional relationship between the two variables, so it can be interpreted that increasing patient knowledge will be directly proportional to the level of PKRS implementation. The conclusion of this study The relationship between knowledge and the implementation of PKRS at RSU. Bina Kasih Medan obtained a p-value of 0.000 which means there is a strong and unidirectional relationship between knowledge and the implementation of PKRS. The more PKRS is implemented in Hospitals, the better the patient's knowledge about the healing process and the regularity of patients in treatment.